International Legal Framework in Curtailing Hazardous COVID-19 Medical Waste: Issues and Challenges - Aidonojie, Paul Atagamen; Aidonojie, Esther Chetachukwu; Okpoko, Mercy Osemudiame; Obieshi, Eregbuonye; Damina, Joshua John (CV. Pustaka Parawali, 2025)
At the close of 2019, the global environment was hit by the COVID-19 pandemic. Healthcare across the global environment was overwhelmed with patients suffering from the COVID-19 virus. However, in a bid to respond in curtailing the COVID-19 pandemic through medical equipment, it resulted in unprecedented waste. However, despite there are several global laws that curtail the incidence of waste generation and disposal, most developing countries experience a high level of medical waste from equipment used in the treatment of COVID-19 patients. In this regard, the study adopts a doctrinal method of investigation to examine the global legal issues and challenges concerning waste emanating from medical equipment in the treatment of COVID-19 patients. The study found that the COVID-19 pandemic resulted in unprecedented medical waste within the global environment, low and middle-income countries suffered more as a dumping ground of medical waste emanating from the equipment used in the treatment of COVID-19 patients. The study also found that there is a legal gaps and weaknesses concerning the international laws curtailing the incidence of waste. Furthermore, the study also found that poor technology in recycling and curtailing COVID-19 medical waste is a major challenge to developing nations during the pandemic. The study concluded and recommended that to ensure a healthy and sustainable environment free from unprecedented waste. There is a need to strengthen National and international laws in curtailing the incidence and indiscriminate dumping of COVID-19 and any medical waste. Furthermore, the study recommends the need for international cooperation in knowledge sharing on sustainable waste management through sophisticated technology.